2021
DOI: 10.34005/lingua.v17i2.1558
|View full text |Cite
|
Sign up to set email alerts
|

Teaching English for Young Learners in Rural Area: Teachers’ Challenges

Abstract: Rural education, in comparison to its urban and suburban counterparts, is seen to face a distinct challenge. The location and implementation of an English curriculum in primary school are significant problems. As a result, the purpose of this study is to look into the difficulties that English teachers face when teaching English to young learners in rural public primary schools in Baureno, East Java. A semi-structured interview with six participants from six elementary schools in five villages (Gajah, Gunungsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 10 publications
(10 reference statements)
2
5
0
Order By: Relevance
“…Because of this, students' socioeconomic backgrounds can have a significant impact not just on their ability to obtain a good education but also on their motivation and attitude toward learning. This aligns with the findings who showed that socio-economic background became one of the problems in teaching English in rural settings (Khulel & Wibowo, 2021). This difficulty occurred as a result of socio-economic background factors such as parental income and educational background.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Because of this, students' socioeconomic backgrounds can have a significant impact not just on their ability to obtain a good education but also on their motivation and attitude toward learning. This aligns with the findings who showed that socio-economic background became one of the problems in teaching English in rural settings (Khulel & Wibowo, 2021). This difficulty occurred as a result of socio-economic background factors such as parental income and educational background.…”
Section: Discussionsupporting
confidence: 90%
“…Based on the data, it found that as local content subject, the status of English can cause problem in time management. This is in line with finding that one of the challenges that confronted by English language teachers when teaching English in primary level the time management issues emerged and it can be influenced with the status of English subject in curriculum (Khulel & Wibowo, 2021). As a result, English has received minimal consideration from teachers.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, English was not a compulsory subject, so the government then decided that elementary schools should implement English depending on the needs of the school. The policy from the Ministry of Education and Culture interested English as a supplementary local subject, which means elementary schools have authority to include English lessons as a subject to teach (Khulel, 2021). Learning English as a foreign language would be beneficial for students as they belong to the golden age.…”
Section: Introductionmentioning
confidence: 99%
“…; access to various information technologies is very limited; and transport infrastructure such as buses, taxis; access to services and facilities such as electricity, water and sanitation; the health, education and economic status of people below the poverty line. Furthermore, rural schools are found to be inferior to their urban counterparts in terms of instruction (Shikalepo, 2020;Khulel, 2021). Moreover, the implementation of English instruction in elementary schools is still constrained by government policies.…”
Section: Introductionmentioning
confidence: 99%